Effectiveness of muscle force and speed of movement carreau shot at distances of 6 and 7-meter petanque sport - Irawan, Fajar Awang; Ramadhan, Ahmad Teguh; Junaidi, Said; Hadi, Hadi; Romadhoni, Syahru; Muhibbi, Muhammad (Universitas Negeri Yogyakarta, 2024)
The problem found is that the point in the shot is not optimal. The study aims to analyze the muscle strength factor / impulse force and speed of movement to produce a carreau shot. The study is a quantitative study with a descriptive approach and survey method, data obtained from the analysis of the kinovea application software version 0.9.4 involving 9 people sample. The results of this study showed a distance of 6 and 7 meters (average ± std. dev), i.e.: 1) muscle strength or pulse 4.73 N ± 0.36 N and 4.58 N ± 0.35 N. 2) movement speed in backswing phase 0.85 m/s ± 0.42 m/s and 0.59 m/s ± 0.27 m/s, swing phase 3.26 m/s ± 0.67 m/s and 3.17 m/s ± 0.78 m/s, and release phase 8.89 m/s ± 0.75 m/s and 8.37 m/s ± 0.58 m/s. The conclusion is that shooting a carreau at a distance of 6 and 7 meters in this study obtained an average score of 17./14 in the middle category with a percentage of 31.5%/25.9%. This study was used as a reference to the trainer making a training program for each athlete to get a high-precision shot.